Balancing refoulement to torture against security interests - the pitfalls of the Suresh exception - Hetaba, Amira (AUC Knowledge Fountain, 2017)
This thesis examines whether the balancing of security interests against refoulement to torture, as advanced by the Canadian Supreme Court in the Suresh Case, is a helpful legal development for negotiating the complex security and protection challenges in the post 9/11 era. This thesis assesses the controversial issues raised by the balancing approach in Suresh and finds the following. Firstly, by allowing refoulement to torture under exceptional circumstances, the Court ignored Canada’s obligations under the Convention against Torture and the absolute prohibition of torture as a norm of ius cogens. This violation of international law through the Suresh exception was influential in foreign jurisdictions. The erosion of the absolute prohibition of torture, in Canada and internationally, is not only illegal but is particularly troubling at a time when security measures infringing human rights, such as extraordinary rendition, are proliferating. Secondly, this thesis analyzes the difficulties of determining who is a threat to national security. Terrorism remains undefined in international law and the Suresh attempt to define the scope of threat domestically raises considerable legal difficulties. For example, it gives rise to the controversial issue of whether an indirect threat to a state is sufficient to justify refoulement to torture, and leaves open what degree of association to a terrorist organization qualifies an individual as a security threat. These debates expose how susceptible the term terrorism is to political manipulation and misuse. Thirdly, this work considers whether there are legal alternatives to the Suresh exception that could better protect national security without undermining the prohibition of refoulement to torture – alternatives better suited to meeting contemporary challenges. This thesis concludes that the Suresh exception is not only unhelpful legally, it is a highly troubling decision that unnecessarily undermines important human rights laws at a time when the opposite is needed.